Design and Characterization of Compact Antennas for Wireless Sensing Applications - Sidibe, Alassane; Loubet, Gael; Takacs, Alexandru; Dragomirescu, Daniela (2020 International Workshop on Antenna Technology (iWAT), 2020)
This paper addresses the design and the characterization of compact antennas designed for wireless sensing applications. More precisely these antennas have to be integrated in the rectenna part of a battery-free and wirelessly powered wireless sensing node embedded in a concrete material. A 3D compact dipole antenna topology is presented, it exhibits at maximum gain of +1.7 dBi at 868 MHz. By integrating this antenna in a metallic cavity, the gain can be enhanced to +4.5 dBi minimizing also the negative impact and the detuning effect of the concrete material on the antenna performances.